Suspended particle device with improved adhesion between active and conductive layers - Patents.com

JP7638002B2Active Publication Date: 2025-03-03GAUZY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022500076
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-02
Filing Date
2020-07-01
Publication Date
2025-03-03
Estimated Expiration
2040-07-01

Smart Images

  • Figure 0007638002000001
    Figure 0007638002000001
  • Figure 0007638002000002
    Figure 0007638002000002
Patent Text Reader

Abstract

A suspended particle device is disclosed that has improved adhesion between an active layer and a conductive layer. The conductive layer is coated with an adhesion promoter that is covalently bonded to the surface of the conductive layer and includes at least one organosilane that includes a crosslinkable moiety, such as an acrylate. The active layer includes a suspension of active particles in a polymer matrix that includes a polymer with pendant crosslinkable moieties, such as an acrylate. Upon curing (e.g., by exposure to ultraviolet light), the polymer matrix of the active layer crosslinks with the crosslinkable moieties of the adhesion promoter, thereby bonding the active layer and the conductive layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Publication References This application claims priority to U.S. Provisional Patent Application Publication No. 62 / 869,597, filed July 2, 2019.

[0002] The present invention relates generally to suspended particle devices (SPDs), and more specifically to SPDs having improved adhesion between the active layer and the conductive layer, and methods for manufacturing such devices. [Background technology]

[0003] A suspended particle device (SPD) is a device for controlling the transmission of light. SPDs typically include an active layer that controls the transmission of light through the device, disposed between two transparent substrates, typically composed of a material such as polyethylene terephthalate (PET), each coated with a transparent conductive layer, typically composed of a material such as tin-doped indium oxide (ITO). SPDs are thus constructed in the general form of a capacitor.

[0004] The active layer comprises an emulsion of a continuous polymer phase and a liquid polymer that is insoluble in the continuous polymer phase. Particles or droplets containing particles that can be reoriented in an external electric field are dispersed in the liquid polymer. In its normal (off) state, no potential is applied to the conductive layer and the active particles are randomly oriented within the droplets or within the polymer matrix. In this state, the light absorption of the device is at its maximum and the transmittance in the visible range is typically below 1%. When a potential is applied to the conductive layer, an electric field is created in the active layer and the particles align with the electric field, thereby increasing the transmittance through the device. A typical SPD has a maximum transmittance of up to 50% in the visible range.

[0005] One parameter that has a significant impact on the durability of SPDs is the adhesion between the active layer and the PET-ITO film substrate. Poor adhesion between the active layer and the conductive layer can, in some cases, cause delamination to such an extent that even slight shear can completely destroy the SPD. As a further example, it is well known in the art that SPDs are sensitive to humidity and poor adhesion can exacerbate this effect, reducing the durability and lifespan of SPDs under practical conditions.

[0006] The adhesion of the continuous polymer phase to the conductive layer determines the overall adhesion of the active layer to the conductive layer, which is typically very limited since the polymer typically lacks any functional groups that can react or interact with the surface of the conductive layer.

[0007] Several attempts to solve this problem have been proposed. For example, US Patent Publication No. 20120236393 discloses an SPD in which the conductive layer comprises a polythiophene-based conductive polymer, such as polyethylenedioxythiophene. The inventors claim that these devices have stronger adhesion between the conductive layer and the active layer than SPDs that use inorganic materials, such as ITO, in the conductive layer. In contrast, US Patent Publication No. 20070195401 discloses an SPD in which the particles in the active layer are suspended in a polymer matrix that includes at least one crosslinked siloxane polymer. The inventors claim that in this case, the polymer matrix composition has better adhesion than compositions previously known in the art.

[0008] Another approach to improving the adhesion of the active layer and the conductive layer has been to coat the conductive layer with a material, such as an adhesive, that will bond the active layer and the conductive layer more strongly to each other. For example, U.S. Patent No. 6,271,956 discloses coating the conductive layer with an adhesive, particularly a polyacrylate-based adhesive, that is inherently tacky at room temperature, thereby bonding the conductive layer to the active layer. U.S. Patent Publication No. 20090153944 discloses coating the conductive layer with a material, such as a TiO 2 or SiOx and an inorganic material having a refractive index greater than 1.54 at 589 nm. US Patent Publication No. 20180074377 discloses the use of an adhesion layer between the conductive layer and the active layer, where the adhesion layer comprises functionalized nanoparticles.

[0009] A third common approach has been the use of silicone-based crosslinkers that, upon curing, provide a covalent bond between the active layer and the conductive layer. For example, Japanese Patent Publication No. 2010237265 discloses an SPD in which an ITO conductive layer is coated with a solid silicone resin. The active layer comprises particles suspended in a polyacrylate matrix. Upon curing, the pendant acryloxy groups in the silicone resin crosslink with the acrylate groups in the active layer matrix, thereby bonding the active layer to the resin.

[0010] Despite these different attempts, there remains a long felt but unmet need for SPDs with improved adhesion between the conductive layer and the active layer. Summary of the Invention

[0011] The invention disclosed herein is designed to address this need. An SPD is disclosed that includes an adhesion promoter disposed between a conductive layer and an active layer. The adhesion promoter comprises molecules that are simultaneously covalently bonded to the surface of the conductive layer and crosslinked with pendant groups of the polymer matrix of the active layer. Although overlapping with other descriptions, various aspects of the present invention are described below, however, the present invention is not limited to the following. [1] A suspended particle device (SPD), comprising: a first transparent outer layer (100) having an outer surface and an inner surface; a first conductive layer (150) having an outer side and an inner side disposed such that the outer side is disposed on the inner side of the first outer transparent layer; a second transparent outer layer (100') having an outer surface and an inner surface; a second conductive layer (150') having an outer side and an inner side disposed such that the outer side is disposed on the inner side of the second outer transparent layer; an active layer comprising a suspension of active particles in a polymer matrix and disposed between the first conductive layer and the second conductive layer, the polymer matrix comprising a polymer comprising at least one pendant crosslinkable side chain; an adhesion promoter disposed on at least one of the inner side of the first conductive layer and the inner side of the second conductive layer, the adhesion promoter comprising at least one crosslinkable moiety; said adhesion promoter being covalently bonded to the surface on which it is disposed; the adhesion promoter and the polymer matrix are crosslinked via the crosslinkable side chains and the crosslinkable moieties; The suspended particle device (SPD). [2] The SPD of [1], wherein at least one of the transparent layers comprises PET. [3] The SPD of [1], wherein at least one of the conductive layers comprises ITO. [4] [1] The SPD according to the present invention, wherein the active particles comprise a polyhalide polarizing material comprising a complex obtained by reacting elemental iodine, a hydrohalic acid or ammonium halide, an alkali metal halide or an alkaline earth metal halide, a first compound comprising pyrazine-2,5-dicarboxylic acid, and a second compound comprising a mono-alkyl ester or mono-amide of pyrazine-2,5-dicarboxylic acid. [5] The SPD according to [1], wherein the active particles are the product of a process comprising reacting, in a suitable liquid elemental iodine, an inorganic halide, a substantially rigid polycyclic precursor compound having two cyclic structures bonded to each other via an aromatic or heteroaromatic group, a three-dimensional structure defined by the two cyclic structures and having only one opening into a cavity, at least one polar group on the exterior of the polycyclic precursor compound, and at least one chelating group for chelating hydrogen or metal ions within the cavity. [6] The SPD of [1], wherein the adhesion promoter is an organosilane covalently bonded to the inner surface of the conductive layer via a Si—O bond. [7] The adhesion promoter has the formula Si(OR 1 ) 3 R 2 (In the formula, R 2 The SPD according to [1], which is an organosilane characterized by: [8] [1] The SPD according to the present invention, wherein the adhesion promoter is a crosslinkable moiety R 2 and at least one OR 1 The formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n The SPD is a polyorganosilane characterized by: [9] The SPD according to [1], wherein the crosslinkable moiety comprises at least one acrylate group.

[10] The SPD according to [1], wherein the crosslinkable side chains contain at least one acrylate group.

[11] A method for manufacturing an SPD, comprising the steps of: obtaining a first surface including a first transparent layer and a first conductive layer disposed on a side of the first transparent layer; obtaining a second surface including a second transparent layer and a second conductive layer disposed on a side of the first transparent layer; preparing a solution of an adhesion promoter comprising at least one crosslinkable moiety; applying the adhesion promoter to at least one of the first conductive layer and the second conductive layer; condensing the adhesion promoter until it is at least partially covalently bonded to the exposed surface of the layer to which it was applied; disposing an active layer comprising a suspension of active particles in a polymer matrix, the polymer matrix comprising at least one polymer comprising crosslinkable pendant groups between the first conductive layer and the conductive layer; and crosslinking the crosslinkable pendant groups and the crosslinkable moieties. The method.

[12] 11. The method of claim 10, wherein at least one of the first transparent layer and the second transparent layer comprises PET.

[13] 12. The method of claim 11, wherein at least one of the first conductive layer and the second conductive layer comprises ITO.

[14] The adhesion promoter has the formula Si(OR 1 ) 3 R 2 (In the formula, R 2 is a crosslinkable organic functional group).

[15] The method according to

[11] , wherein the adhesion promoter is a crosslinkable moiety R 2 and at least one OR 1 The formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n The polyorganosilane is characterized by:

[16] The method of claim 11, wherein the crosslinkable moiety is an acrylate.

[17] 12. The method of claim 11, wherein the step of applying the adhesion promoter comprises applying the adhesion promoter by a method selected from the group consisting of spraying and gravure coating.

[18] 12. The method of claim 11, wherein the condensing step comprises heating the surface and the adhesion promoter until the adhesion promoter is at least partially covalently bonded to the conductive layer.

[19] The method of claim 11, wherein the crosslinkable pendant groups comprise an acrylate.

[20] The method of claim 11, wherein the curing step comprises irradiating with ultraviolet light until the crosslinkable moieties and the crosslinkable pendant groups are at least partially crosslinked.

[21] 12. The method of claim 11, wherein the curing step comprises curing until the cross-linkable moieties and the cross-linkable pendant groups are sufficiently cross-linked such that the adhesion between the active layer and the conductive layer is at least 0.1 N / inch.

[22] 12. The method of claim 11, wherein the curing step comprises curing until the cross-linkable moieties and the cross-linkable pendant groups are sufficiently cross-linked such that the adhesion between the active layer and the conductive layer is at least 0.2 N / inch.

[23] The method of claim 11, wherein the curing step includes curing until the crosslinkable moieties and the crosslinkable pendant groups are sufficiently crosslinked to provide an adhesive strength between the active layer and the conductive layer of 0.1 N / inch to 0.3 N / inch.

[24] The SPD according to [1], produced according to the method described in

[11] .

[0012] Accordingly, it is an object of the invention disclosed herein to provide an SPD comprising: a first transparent outer layer (100) having an outer surface and an inner surface; a first conductive layer (150) having an outer surface and an inner surface disposed such that the outer surface is disposed on the inner surface of the first transparent outer layer; a second transparent outer layer (100') having an outer surface and an inner surface disposed such that the outer surface is disposed on the inner surface of the second transparent outer layer; an active layer comprising a suspension of active particles in a polymer matrix and disposed between the first conductive layer and the second conductive layer, the polymer matrix comprising a polymer comprising at least one pendant crosslinkable side chain; and an adhesion promoter disposed on at least one of the inner surface of the first conductive layer and the inner surface of the second conductive layer, the adhesion promoter comprising at least one crosslinkable moiety. It is within the spirit of the invention that the adhesion promoter is covalently bonded to the surface on which it is disposed, and that the adhesion promoter and the polymer matrix are crosslinked via the crosslinkable side chains and the crosslinkable moieties.

[0013] It is a further object of the present invention to disclose such an SPD, wherein at least one of said transparent layers comprises PET.

[0014] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein at least one of said conductive layers comprises ITO.

[0015] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said active particles comprise a polyhalide polarizing material comprising a complex obtained by reacting elemental iodine, a hydrohalic acid or ammonium halide, an alkali metal halide or an alkaline earth metal halide, a first compound comprising pyrazine-2,5-dicarboxylic acid, and a second compound comprising a mono-alkyl ester or mono-amide of pyrazine-2,5-dicarboxylic acid.

[0016] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said active particles are the product of a process comprising reacting in a suitable liquid elemental iodine an inorganic halide, a substantially rigid polycyclic precursor compound having two cyclic structures bonded to each other via an aromatic or heteroaromatic group, a three-dimensional structure defined by said two cyclic structures and having only one opening into a cavity, at least one polar group on the exterior of the polycyclic precursor compound, and at least one chelating group for chelating hydrogen or metal ions within the cavity.

[0017] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said adhesion promoter is an organosilane covalently bonded to said inner surface of said conductive layer via a Si—O bond.

[0018] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said adhesion promoter has the formula Si(OR 1 ) 3 R 2 (In the formula, R 2 is a crosslinkable organic functional group.

[0019] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said adhesion promoter comprises at least one crosslinkable moiety R 2 and at least one OR 1The formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n It is a polyorganosilane characterized by:

[0020] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said crosslinkable moiety comprises at least one acrylate group.

[0021] It is a further object of the present invention to disclose an SPD as defined in any of the above, wherein said crosslinkable side chains comprise at least one acrylate group.

[0022] It is a further object of the present invention to disclose a method for producing an SPD, the method comprising the steps of obtaining a first surface comprising a first transparent layer and a first conductive layer disposed on a side of the first transparent layer, obtaining a second surface comprising a second transparent layer and a second conductive layer disposed on a side of the first transparent layer, preparing a solution of an adhesion promoter comprising at least one crosslinkable moiety, applying the adhesion promoter to at least one of the first conductive layer and the second conductive layer, condensing the adhesion promoter until it is at least partially covalently bonded to the exposed surface of the layer to which the adhesion promoter was applied, disposing an active layer comprising a suspension of active particles in a polymer matrix, the polymer matrix comprising at least one polymer comprising crosslinkable pendant groups between the first conductive layer and the conductive layer, and crosslinking the crosslinkable pendant groups and the crosslinkable moieties.

[0023] It is a further object of the present invention to disclose such a method, wherein at least one of said first transparent layer and said second transparent layer comprises PET.

[0024] It is a further object of the present invention to disclose a method as defined in any of the above, wherein at least one of said first and second conductive layers comprises ITO.

[0025] It is a further object of the present invention to disclose a method as defined in any of the above, wherein said adhesion promoter is of the formula Si(OR 1 ) 3 R 2 (In the formula, R 2 is a crosslinkable organic functional group.

[0026] It is a further object of the present invention to disclose a method as defined in any of the above, wherein said adhesion promoter comprises a compound in which each silicon atom is linked to at least one crosslinkable moiety R 2 and at least one OR 1 The formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n It is a polyorganosilane characterized by:

[0027] It is a further object of the present invention to disclose the method as defined in any of the above, wherein said crosslinkable moieties are acrylates.

[0028] It is a further object of the present invention to disclose the method as defined in any of the above, wherein said step of applying said adhesion promoter comprises applying said adhesion promoter by a method selected from the group consisting of spraying and gravure coating.

[0029] It is a further object of the present invention to disclose a method as defined in any of the above, wherein said condensing step comprises heating said surface and said adhesion promoter until said adhesion promoter is at least partially covalently bonded to said conductive layer.

[0030] It is a further object of the present invention to disclose the method as defined in any of the above, wherein said crosslinkable pendant groups comprise acrylates.

[0031] It is a further object of the present invention to disclose a method as defined in any of the above, wherein said curing step comprises irradiating with ultraviolet light until said crosslinkable moieties and said crosslinkable pendant groups are at least partially crosslinked.

[0032] It is a further object of the present invention to disclose the method as defined in any of the above, wherein said curing step comprises curing until said crosslinkable moieties and said crosslinkable pendant groups are sufficiently crosslinked such that the adhesion between said active layer and said conductive layer is at least 0.1 N / inch.

[0033] It is a further object of the present invention to disclose the method as defined in any of the above, wherein said curing step comprises curing until said crosslinkable moieties and said crosslinkable pendant groups are sufficiently crosslinked such that the adhesion between said active layer and said conductive layer is at least 0.2 N / inch.

[0034] It is a further object of the present invention to disclose the method as defined in any of the above, wherein said curing step comprises curing until said crosslinkable moieties and said crosslinkable pendant groups are sufficiently crosslinked such that the adhesion between said active layer and said conductive layer is between 0.1 N / inch and 0.3 N / inch.

[0035] It is a further object of the present invention to disclose an SPD as defined in any of the above, produced by a method as defined in any of the above.

[0036] Next, the present invention will be described with reference to the drawings. [Brief description of the drawings]

[0037] [Figure 1]1 shows a schematic chemical structure of an adhesion promoter covalently bonded to a conductive layer of an SPD according to one non-limiting embodiment of the invention disclosed herein.

[0038] [Diagram 2] 1 illustrates a schematic diagram of crosslinking of pendant groups of an adhesion promoter covalently bonded to a conductive layer of an SPD to pendant groups of an active layer, according to one non-limiting embodiment of the invention disclosed herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] In the following description, various aspects of the invention are described. For the purpose of explanation, specific details are described to provide a thorough understanding of the invention. It will be apparent to those skilled in the art that there are other embodiments of the invention in which the details differ without affecting the essential nature of the invention. Thus, the present invention is not limited by what is shown in the drawings and described herein, but only by what is set forth in the appended claims, the appropriate scope being determined only by the broadest interpretation of said claims. In some cases, for clarity or conciseness, individual elements of the invention are described separately. Nevertheless, the inventors consider any combination of the elements of the invention disclosed herein that is not self-contradictory to be within the scope of the invention.

[0040] As used herein, the abbreviation "SPD" stands for "Suspended Particle Device."

[0041] As used herein, the abbreviation "PET" stands for "polyethylene terephthalate."

[0042] As used herein, the abbreviation "ITO" stands for "indium tin oxide."

[0043] As used herein, the term "active particles" refers to particles of a material that, when suspended in a suitable medium, reorients itself upon application of an external electric field; when a suspension of active particles, in which the particles are randomly oriented in the absence of an external electric field, is exposed to an external electric field, the particles tend to align with the field, thereby changing the optical properties of the suspension, such as the visible light transmittance. Active particles are typically rod- or needle-shaped. Non-limiting examples of active particles known in the art are TiO 2 and Fe 2 O 3 H 2 Metal oxides such as CoAl 2 O 4 and the like, alkali halides, as well as alkali oxides.

[0044] Unless otherwise stated, with respect to numerical values, the term "about" is used to indicate a range of ±20% of the nominal value.

[0045] The invention disclosed herein provides a novel solution to the problem of poor adhesion between the conductive layer and the active layer, which limits the resilience and lifespan of typical SPDs. The SPDs of the present invention include an adhesion promoter between the conductive layer and the active layer. The adhesion promoter is covalently bonded to the surface of the conductive layer and is crosslinked to the polymers that comprise the polymer matrix of the active layer. By being covalently bonded to both layers, the adhesion promoter acts to chemically bond to the conductive layer and the active layer, providing a much stronger bond than the physical adhesion between the layers in SPDs known in the art.

[0046] Reference is now made to FIG. 1, which illustrates a schematic of one non-limiting embodiment of the bonding of an adhesion promoter to a conductive layer. A conductive layer 150 is disposed on a transparent outer layer 100. In an exemplary embodiment of the invention, the transparent outer layer is made of PET and the conductive layer is made of ITO, although any material known in the art suitable for use in fabricating SPDs can be used. An adhesion promoter 200 containing at least one crosslinkable functional group is covalently bonded to the exposed surface of the conductive layer leaving the crosslinkable functional group exposed. In some non-limiting embodiments of the invention, such as those illustrated in FIG. 1, the adhesion promoter has the general formula Si(OR 1 ) 3 R 2 wherein R 1 may be hydrogen or an organic functional group such as an alkyl group, and R 2 is a crosslinkable organic functional group. In some preferred embodiments of the present invention, the crosslinkable organic functional group is an acrylate, as shown in Figure 1. As shown in Figure 1, the crosslinkable organic functional group has the general formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n Adhesion promoters comprising polysilanes of the formula: are considered by the inventors to be within the scope of the present invention. The adhesion promoter is chemically bonded to the top surface of the conductive layer. When the adhesion promoter is an organosilane and the conductive layer is an oxide such as ITO, the adhesion promoter is bonded to the surface of the conductive layer by Si-O-[surface] bonds created by condensation of the organosilane with the surface of the oxide.

[0047] Reference is now made to Figure 2, which shows a schematic diagram of bonding between an active layer and a conductive layer via an adhesion promoter. The SPD includes two transparent layers 100 and 100', each having a conductive layer (150 and 150', respectively) disposed on its inner surface. An adhesion promoter is disposed on the inner surface of at least one of the conductive layers, and preferably both of them. Crosslinkable groups R (210) of the adhesion promoter are shown diagrammatically protruding from the surface.

[0048] An active layer 300 containing a suspension of active particles (or droplets containing active particles) is disposed between the two conductive layers. Any type of active particles known in the art can be used. In some preferred embodiments of the invention, the active particles include at least one of the polyhalide polarizing materials disclosed in U.S. Pat. No. 6,517,746, the entirety of which is incorporated herein by reference. In a non-limiting example of this embodiment, the active particles include a complex obtained by reacting elemental iodine, a hydrohalic acid or ammonium halide, an alkali metal halide or an alkaline earth metal halide, a first compound containing pyrazine-2,5-dicarboxylic acid, and a second compound containing a monoalkyl ester or monoamide of pyrazine-2,5-dicarboxylic acid. In some other preferred examples of the invention, the active particles include at least one of the polyhalide polarizing materials disclosed in European Patent No. 1,056,974, the entirety of which is incorporated herein by reference. In a non-limiting example of this embodiment, the active particles are prepared by a process that includes reacting in a suitable liquid elemental iodine an inorganic halide, a substantially rigid polycyclic precursor compound having two ring structures bonded to each other via an aromatic or heteroaromatic group, a three-dimensional structure defined by the two ring structures and having only one opening into a cavity, at least one polar group on the exterior of the polycyclic precursor compound, and at least one chelating group for chelating hydrogen or metal ions within the cavity.

[0049] The polymer matrix comprises a polymer having pendant crosslinkable moieties, shown diagrammatically as protruding from the matrix (310). In an exemplary embodiment of the invention, the pendant crosslinkable moieties also comprise acrylate groups.

[0050] After the initial assembly of the SPD, a reaction is initiated between the crosslinkable moieties of the adhesion promoter and the crosslinkable moieties of the polymer matrix, crosslinking the pendant groups of the polymer matrix with the crosslinkable moieties of the adhesion promoter, thereby yielding an SPD with crosslinked active and conductive layers (330).

[0051] In typical embodiments of the invention, the adhesion between the active layer and the conductive layer is at least 0.1 N / inch. In preferred embodiments of the invention, the adhesion between the active layer is between 0.1 N / inch and 0.3 N / inch. In particularly preferred embodiments of the invention, the adhesion between the active layer is about 0.2 N / inch. EXAMPLES

[0052] The following examples are intended to assist one of ordinary skill in making and using the invention disclosed herein, and are not intended to be limiting in any way.

[0053] example A solution containing the adhesion promoter was prepared by adding 4 g of 3-(trimethoxysilyl)propyl methacrylate to a bottle containing 200 ml of an ethanol / water mixture (approximately 95% ethanol) and mixing with a magnetic stirrer for 30 minutes.

[0054] To obtain PET-ITO (i.e., a PET film coated with a layer of ITO), the solution obtained in the previous step was applied on top of the ITO layer. The amount of solution applied to the surface was approximately 30-40 g / m 2 The PET-ITO-silane was then heated to 110 °C until the silane and oxide surface condensed, releasing water and producing a cured PET-ITO-silane film in which the silane was bonded to the ITO by Si-O-[surface] bonds.

[0055] An SPD was then constructed from two cured PET-ITO-silane films and an active layer containing active particles suspended in a polyacrylate polymer by placing the active layer between the two cured PET-ITO-silane films and irradiating the assembly with UV light until the adhesion promoter and polymer matrix were crosslinked.

Claims

1. 1. A suspended particle device (SPD) comprising: a first transparent outer layer (100) having an outer surface and an inner surface; a first conductive layer (150) having an outer side and an inner side disposed such that the outer side is disposed on the inner surface of the first outer transparent layer; a second transparent outer layer (100') having an outer surface and an inner surface; a second conductive layer (150') having an outer side and an inner side disposed such that the outer side is disposed on the inner surface of the second outer transparent layer; an active layer comprising a suspension of active particles in a polymer matrix and disposed between the first conductive layer and the second conductive layer, the polymer matrix comprising a polymer comprising at least one pendant crosslinkable side chain; an adhesion promoter disposed on at least one of the inner side of the first conductive layer and the inner side of the second conductive layer, the adhesion promoter comprising at least one crosslinkable moiety; the adhesion promoter is covalently bonded to the interior of the conductive layer on which it is disposed; the adhesion promoter and the polymer matrix are crosslinked via the at least one pendant crosslinkable side chain and the at least one crosslinkable moiety; The suspended particle device (SPD).

2. The SPD of claim 1 , wherein at least one of said transparent outer layers comprises PET.

3. The SPD of claim 1 , wherein at least one of said conductive layers comprises ITO.

4. 2. The SPD of claim 1, wherein the active particles are: active particles comprising a polyhalide light-polarizing material comprising a complex obtained by reacting elemental iodine, a hydrohalic acid or ammonium halide, an alkali metal halide or an alkaline earth metal halide, a first compound comprising pyrazine-2,5-dicarboxylic acid, and a second compound comprising a mono-alkyl ester or mono-amide of pyrazine-2,5-dicarboxylic acid; Active particles that are the product of a process that includes reacting in a suitable liquid elemental iodine an inorganic halide, a substantially rigid polycyclic precursor compound having two cyclic structures bonded together via an aromatic or heteroaromatic group, a three-dimensional structure defined by said two cyclic structures and having only one opening into a cavity, at least one polar group on the exterior of said polycyclic precursor compound, and at least one chelating group for chelating hydrogen or metal ions within said cavity. The SPD is selected from the group consisting of:

5. 2. The SPD of claim 1, wherein said adhesion promoter is an organosilane covalently bonded to said inner surface of said conductive layer via a Si-O bond.

6. The adhesion promoter is Formula Si(OR 1 ) 3 R 2 (In the formula, R 2 is a crosslinkable organic functional group, and The formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n wherein each silicon atom is linked to at least one crosslinkable moiety R 2 and at least one OR 1 wherein successive silicon atoms are bonded to an oxygen atom, and 2. The SPD of claim 1, which is an organosilane selected from the group consisting of:

7. 2. The SPD of claim 1, wherein at least one of said crosslinkable moieties and said pendant crosslinkable side chains comprises at least one acrylate group.

8. 1. A method for producing an SPD, comprising the steps of: obtaining a first surface including a first transparent layer and a first conductive layer disposed on a side of the first transparent layer; obtaining a second surface including a second transparent layer and a second conductive layer disposed on a side of the first transparent layer; preparing a solution of an adhesion promoter comprising at least one crosslinkable moiety; applying the adhesion promoter to at least one of the first conductive layer and the second conductive layer; condensing the adhesion promoter until it is at least partially covalently bonded to exposed surfaces of at least one of the first conductive layer and the second conductive layer to which the adhesion promoter has been applied; disposing an active layer comprising a suspension of active particles in a polymer matrix, the polymer matrix comprising at least one polymer comprising crosslinkable pendant groups between the first conductive layer and the conductive layer; crosslinking said crosslinkable pendant groups and said crosslinkable moieties; The method according to claim 1, further comprising:

9. The method of claim 8 , wherein at least one of the first transparent layer and the second transparent layer comprises PET.

10. 9. The method of claim 8, wherein at least one of the first and second conductive layers comprises ITO.

11. The adhesion promoter is Formula Si(OR 1 ) 3 R 2 (In the formula, R 2 is a crosslinkable organic functional group, and The formula [(OR 1 ) x R 2 Si-O-SiR 2 (OR 1 ) x ] n wherein each silicon atom is linked to at least one crosslinkable moiety R 2 and at least one OR 1 wherein successive silicon atoms are bonded to an oxygen atom, and 9. The method of claim 8, wherein the organosilane is selected from the group consisting of:

12. The method of claim 8, wherein the crosslinkable moiety is an acrylate.

13. 9. The method of claim 8, wherein the condensing step comprises heating the surface and the adhesion promoter until the adhesion promoter is at least partially covalently bonded to the conductive layer.

14. The method of claim 8, wherein the crosslinkable pendant groups comprise an acrylate.

15. 9. The method of claim 8, wherein the crosslinking step includes curing until the crosslinkable moieties and the crosslinkable pendant groups are sufficiently crosslinked to provide an adhesion between the active layer and the conductive layer of at least 0.1 N / inch.

Citation Information

Patent Citations

  • Preparation method of suspended particle controllable light valve

    CN109856884A

  • Production of uv curing optical modulation film for light valve

    JP1999218789A

  • Film for suspended particle device, and method of manufacturing the same

    JP2010237265A

  • SPD films formed with conductive polymer-coated substrates

    US20120236393A1

  • Light control film

    WO2009093657A1